Effect of Baggase Physical Properties and Composition on Flame Spread Behavior - Razali, Mohd Azahari; Sapit, Azwan; Mohammad, Akmal Nizam; Salleh, Hamidon; Madon, Rais Hanizam (International Journal of Integrated Engineering, 2020)
Fire Safety Engineering is an application of science to improve the safety from the destructive effect of the fire. Paper is well known as a material that can easily catch fire. Nowadays, many researchers have been interested to produce paper by using other natural fiber to reduce the usage of wood as raw material for paper production. However, research on flame spread towards combination paper / natural fiber is still a lack of data. Inspiration from this, the behavior of downward flame spread over paper and bagasse is experimentally investigated. This experiment is conducted by using the specimen with different thickness and different composition of bagasse. Specimen thickness is chosen at 0.7mm, 1.4mm, 2.1mm and 2.8mm; while for bagasse composition is 0%, 30%, 50%, 70% and 100%. Flame spread behavior for each specimen is videotaped by using a camera. The result showed that the flame spreads with â€œUâ€ pattern at the beginning of the combustion, but end up with different pattern according to thickness and composition of bagasse. It is seen that flame spread rate decreases with increasing the thickness and composition of bagasse for the specimen. The result also shows that up to 70% bagasse, the flame spread rate is approximately constant even for different thickness.